2003
DOI: 10.1074/jbc.m301938200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 Plays a Pivotal Role in the Inhibitory Effect of Lipopolysaccharide and Interleukin-1β on Long Term Potentiation in Rat Dentate Gyrus

Abstract: Lipopolysaccharide (LPS), a component of the cell wall of Gram-negative bacteria, has been shown to induce profound changes both peripherally and centrally. It has recently been reported that intraperitoneal injection of LPS inhibited long term potentiation (LTP) in perforant path-granule cell synapses and that this effect was coupled with an increase in the concentration of the proinflammatory cytokine, interleukin-1␤ (IL-1␤). The LPS-induced effects were abrogated by inhibition of caspase-1, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 67 publications
12
116
1
Order By: Relevance
“…Enhanced activation of both have been reported in aged animals, and following LPS or A␤ administration, and is associated with impaired LTP Kelly et al, 2003;Minogue et al, 2003;Costello and Herron, 2004;Barry et al, 2005). Similarly, inhibition of JNK or NF-B alleviates the depression of LTP observed in response to LPS and/or A␤ (Kelly et al, 2003;Minogue et al, 2003;Costello and Herron, 2004;Barry et al, 2005). Interestingly, the evidence indicates that wedelolactone, which inhibits NF-B activation (Kobori et al, 2004), increases LTP above control levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Enhanced activation of both have been reported in aged animals, and following LPS or A␤ administration, and is associated with impaired LTP Kelly et al, 2003;Minogue et al, 2003;Costello and Herron, 2004;Barry et al, 2005). Similarly, inhibition of JNK or NF-B alleviates the depression of LTP observed in response to LPS and/or A␤ (Kelly et al, 2003;Minogue et al, 2003;Costello and Herron, 2004;Barry et al, 2005). Interestingly, the evidence indicates that wedelolactone, which inhibits NF-B activation (Kobori et al, 2004), increases LTP above control levels.…”
Section: Discussionmentioning
confidence: 91%
“…Investigations into the mechanisms underlying these inflammatory processes have illustrated that proinflammatory cytokines induce an impairment in hippocampal-dependent memory (Barrientos et al, 2002;Hein et al, 2010) and LTP Curran and O'Connor, 2001). Additionally, inflammatory challenges associated with age, ␤-amyloid, or lipopolysaccharide (LPS) elicit similar deficits in LTP through activation of stress-activated protein kinases Kelly et al, 2003;Minogue et al, 2003;Costello and Herron, 2004;Barry et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we considered two different kinases, namely JNK and p38 MAPK as potentially involved in inhibition of LTP. Recent results showed that p38 MAPK and JNK activation are required for LTP inhibition induced by proinflammatory agents such as interleukin-1␤ and lipopolysaccharide (Curran et al, 2003;Kelly et al, 2003). These results prompted us to test whether p38 MAPK and JNK were involved in LTP inhibition by A␤.…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglial cells produce a wide spectrum of proinflammatory and cytotoxic factors, including TNF-␣ and IL-1␤ (for review, see Simm et al, 2004), two cytokines implicated in AD pathogenetic mechanisms (Akiyama et al, 2000). Importantly, IL-1␤ is implicated in disruption of synaptic efficacy induced by proinflammatory agents (Curran et al, 2003;Kelly et al, 2003). Moreover, in the hippocampus, IL-1␤ induced synaptic depression, inhibiting the subsequent induction of LTD in response to a 1 Hz electrical stimulation (Ikegaya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial RAGE has been implicated in the development of inflammatory response and cellular dysfunction (Lue et al, 2001;Bianchi et al, 2010). Cytokines, in particular IL-1␤ and TNF-␣, released by microglial cells, are key molecules that are capable of modulating synaptic function and plasticity (Coogan et al, 1999;Ikegaya et al, 2003;Kelly et al, 2003;Pickering et al, 2005). To test the possible involvement of cytokines, we first tried to mimic A␤-dependent synaptic depression by exogenously applying IL-1␤ (1 ng/ml) and TNF-␣ (5 ng/ml) on slices for 10 min.…”
Section: A␤-dependent Synaptic Depression and Ltd Inhibition Is Mimicmentioning
confidence: 99%